Islam, the Middle East, and the new global hegemony - Murden, Simon (Middle East in the international system, 2002)
Simon Murden investigates how Muslim societies in the Middle East are being affected by globalized politics and economics and how they are adapting to it. Murden describes how a Western-designed set of economic and political norms, institutions and regimes has come to be a hegemonic system. His focus is on the encounter between the Islamic vision of society, with its emphasis on community and social control, and the Western liberal vision of economic liberation and individual choice. Attempting to make sense of the various political purposes to which Islam is being put in Middle Eastern states, he explores the response of the Islamic world to the penetration of the liberal political agenda. Moving the debate beyond the polarization engendered by the "clash of civilizations" thesis, Murden reveals the complex interactions between Islam and the West that are shaping Middle Eastern politics.